Challenges in Communication about Covid Medical Risks: : A Speculative Educational Template - Meldrum, Helen; Hardy, Mary (International Journal of Practice-based Learning in Health and Social Care, 2023)
The most recent descriptions of how the pandemic is playing out in medical offices and hospitals describe scenarios that are truly unprecedented. The impact of COVID-19 on individuals sick enough to seek professional health care highlights the importance of communication skills in explaining potential risks. Clinicians need to be sophisticated in thinking about how to approach each patient. We propose an educational framework for pre-service and in-service health care professionals to improve communication skills during this crisis. To assist Covid patients and their family members, clinicians need to be mindful of the ways that the likelihood of serious impact and consequences of treatments are perceived by each patient and their loved ones. The four-quadrant scheme we offer is a way to help providers orient themselves to their task and prepare to speak effectively about medical choices related to Covid. It is obvious that most situations demand more than one type of communication competency, but the focus here is on what might be advisable as the primary or “lead” skill. Thinking through what would be the preferred “leading” strategies is crucial for clinicians aiming to help COVID-19 patients think about the risks they are facing. Addressing the psychological state of each individual patient is vital. The most important element in managing COVID-19 is to empower patients with the appropriate information and emotional support. Additionally, we hope this model will inspire health professions faculty to think in new ways about teaching and coaching options in the practice-based learning of communication skills.